Association of lifestyle habits and diet quality with the body image perception of selected women of reproductive age (18-25 years) in urban areas of Yangon, Myanmar - Htun, Thwal
Body image perception affects the physical, emotional, and mental wellbeing of an individual. Women of Reproductive Age (WRA) are more susceptible to a negative body image perception that affects their diet quality and lifestyle habits. Myanmar is currently in a coup d'etat that significantly impacted the diet quality of the population. This study investigated the association between the demographic characteristics, lifestyle habits, and diet quality with the body image perception of women aged 18-25 years old. This study was conducted in urban areas of Yangon in Myanmar through an online data collection using an analytical cross-sectional study research design. Convenience sampling was employed to recruit 602 respondents. Stunkard Figure Rating Scale (SFRS) was used to determine the body size of the respondents, while questions extracted from Minimum Dietary Diversity-Women (MDD-W) Questionnaire, International Physical Activity Questionnaire (IPAQ) were used to determine the diet quality and physical activity of the respondents, respectively. Respondents with full-time employment were most likely to have an unacceptable diet quality due to time constraints. Higher educational attainment positively influenced diet quality as well. Marital status and income level had positive effects on the diet quality of the respondents, however, there was no sufficient evidence to conclude if there was an association between lifestyle habits and diet quality with body image perception of the study respondents.